3D‐printing carbon nanotubes/Ti3C2Tx/chitosan composites with different arrangement structures based on ball milling for EMI shielding. Issue 45 (23rd September 2022) - Pei, Xiaoyuan; Liu, Guangde; Shao, Ruiqi; Yu, Rongrong; Chen, Runxiao; Liu, Dong; Wang, Wei; Min, Chunying; Liu, Shengkai; Xu, Zhiwei
Abstract: Conductive macroscopic MXene‐based architectures receive tremendous attention for various potential applications. In this paper, the rheology and printing suitability of MXene ink were optimized by ball milling method to ensure good structural integrity and electrical conductivity of the printing structure. Porous CNT/Ti3 C2 Tx /CS composites were prepared by 3D printing, and the effects of various arrangements on electromagnetic interference shielding (EMI SE) were studied in depth. Since Ti3 C2 Tx can produce TiO2 under the action of high‐energy ball milling, it provides more heterogeneous interfaces and dipole effects. At the same time, Ti3 C2 Tx and CNT are evenly dispersed and can construct a complete conductive network, which greatly enhances its conductivity loss. In collaboration with the 3D‐printed framework, it can also extend the propagation path of electromagnetic waves and enhance their multiple reflection losses. The results show that the EMI SE of the composite material can reach 26 dB in X‐band, and EMI SE can be affected by the different arrangement. This work lays a solid foundation for the construction of heterogeneous interfaces by ball milling and the free construction of EMI shielding materials by 3D printing. Abstract :